Impact of a Terahertz electromagnetic field on the ion permeation of potassium and sodium channels - Zigang Song; Lingfeng Xue; Qi Ouyang; Chen Song (Communications Chemistry)
Abstract Ion channels are essential for various physiological processes, and their defects are associated with many diseases. Previous research has revealed that a Terahertz electromagnetic field can alter the channel conductance by affecting the motion of chemical groups of ion channels, and hence regulate the electric signals of neurons. In this study, we conducted molecular dynamics simulations to systematically investigate the effects of terahertz electromagnetic fields on the ion permeation of voltage-gated potassium and sodium channels, particularly focusing on the bound ions in the selectivity filters that have not been extensively studied previously. Our results identified multiple new characteristic frequencies and showed that 1.4, 2.2, or 2.9 THz field increases the ion permeability of Kv1.2, and 2.5 or 48.6 THz field increases the ion permeability of Nav1.5. Such effects are specific to the frequencies and directions of the electric field, which are determined by the intrinsic oscillation motions of the permeating ions in the selectivity filter or certain chemical groups of the ion channels. The amplitude of the THz field positively correlates with the change in ion permeation. This study demonstrates that THz fields can specifically regulate ion channel conductances by multiple mechanisms, which may carry great potential in biomedical applications.